An Unsteady State Tracer Method for Characterizing Fractures in Bedrock Wells. Issue 1 (29th March 2013) - Libby, Jill L.; Robbins, Gary A.
Abstract Evaluating contaminants impacting wells in fractured crystalline rock requires knowledge of the individual fractures contributing water. This typically involves using a sequence of tools including downhole geophysics, flow meters, and straddle packers. In conjunction with each other these methods are expensive, time consuming, and can be logistically difficult to implement. This study demonstrates an unsteady state tracer method as a cost‐effective alternative for gathering fracture information in wells. The method entails introducing tracer dye throughout the well, inducing fracture flow into the well by conducting a slug test and then profiling the tracer concentration in the well to locate water contributing fractures where the dye has been diluted. By monitoring the development of the dilution zones within the wellbore with time, the transmissivity and the hydraulic head of the water contributing fractures can be determined. Ambient flow conditions and the contaminant concentration within the fractures can also be determined from the tracer dilution. This method was tested on a large physical model well and a bedrock well. The model well was used to test the theory underlying the method and to refine method logistics. The approach located the fracture and generated transmissivity values that were in excellent agreement with those calculated by slug testing. For the bedrock well tested, two major active fractures were located. Fracture location and ambient well conditions matched results from conventional methods. Estimates of transmissivity values by the tracer method were within an order of magnitude of those calculated using heat‐pulse flow meter data.